2013
DOI: 10.14417/lp.688
|View full text |Cite
|
Sign up to set email alerts
|

8 ou 80! Adaptação e validação da Escala Breve de Intensidade Afectiva

Abstract: Resumo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
(35 reference statements)
1
2
0
2
Order By: Relevance
“…The findings are in agreement with the original version of the instrument (Geuens & De Pelsmacker, 2002) and with another adapted version, the Portuguese version (Prada et al, 2009). The procedures adopted in this study for the translation of the instrument point to evidence of validity based on the content of the items.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The findings are in agreement with the original version of the instrument (Geuens & De Pelsmacker, 2002) and with another adapted version, the Portuguese version (Prada et al, 2009). The procedures adopted in this study for the translation of the instrument point to evidence of validity based on the content of the items.…”
Section: Discussionsupporting
confidence: 85%
“…The SAIS has the advantage of being reduced; that is, it demands little time from the respondents and presents adequate validity and reliability indicators. An adaptation study for a Portuguese sample also found adequate psychometric properties for SAIS, including the three-factor structure (Prada et al, 2009). A Brazilian version of the scale would make for new research and advances regarding this construct.…”
Section: Measurement Of Affect Intensitymentioning
confidence: 85%
See 1 more Smart Citation
“…A SAIS apresenta a vantagem de ser reduzida, ou seja, demanda pouco tempo dos respondentes e apresenta adequados indicadores de validade e fidedignidade. Um estudo de adaptação para uma amostra portuguesa também encontrou propriedades psicométricas adequadas para a SAIS, incluindo-se a estrutura de três fatores (Prada et al, 2009). Uma versão brasileira da escala possibilitaria novas pesquisas e avanços a respeito desse construto.…”
Section: Mensuração Da Intensidade De Afetosunclassified
“…Essas versões reformuladas também indicaram que o modelo multifatorial superava estruturalmente o modelo unidimensional. Mais recentemente, Geuens e De Pelsmacker (2002) desenvolveram uma versão simplificada da AIM, a Short Affect Intensity Scale (SAIS), adaptando-a de forma que os itens se referissem apenas à intensidade afetiva(Prada et al, 2009).A Short Affect Intensity Scale (SAIS -Geuens & De Pelsmacker, 2002) é composta por 20 itens, extraídos dentre os 40 do instrumento original de Larsen e Diener (1987). A medida acessa três fatores concernentes à intensidade dos afetos: Intensidade Positiva, Intensidade Negativa, e Serenidade.…”
unclassified